Aerobic Dimerization of Enediyne Compounds: Construction of Naphthalene Frameworks. Issue 1 (25th November 2015) - Wang, Dongxu; Ling, Fei; Liu, Xiang; Li, Zexiang; Ma, Cheng
Abstract: The first bimolecular oxygenative annulation of enediyne compounds leading to naphthalene frameworks has been developed by using Pd(OAc)2 as the catalyst in the presence of NaI under O2 (1 atm). This reaction provided efficient access to a class of symmetric core‐annulated naphthalenes by the homoannulation of enediyne–imides. Intriguingly, the crossover annulation of enediyne–imides and other functionalized enediynes could also be achieved by the same catalytic system, resulting in the formation of several unsymmetrical naphthalene derivatives. Preliminary mechanistic investigation using 18 O isotopic labelling and radical scavengers indicated that radical oxygen incorporation cascades might be involved in this conversion. Abstract : De novo‐selectivity! A Pd II ‐catalyzed bimolecular aerobic oxidative annulation of enediyne compounds using O2 (1 atm) in the presence of NaI is presented (see scheme; Ts=toluene‐4‐sulfonyl) that gives access to a class of symmetric naphthalene derivatives and several unsymmetrical naphthalene products containing up to six fully differentiated substituents in a regioisomer‐free mode.